If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2B + -11 = 88 Reorder the terms: -11 + 2B = 88 Solving -11 + 2B = 88 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 2B = 88 + 11 Combine like terms: -11 + 11 = 0 0 + 2B = 88 + 11 2B = 88 + 11 Combine like terms: 88 + 11 = 99 2B = 99 Divide each side by '2'. B = 49.5 Simplifying B = 49.5
| -4/7x=16/27 | | 2v+1=10 | | 2x^2+2x+75=0 | | y/4=14 | | (2+w)(4w-5)=0 | | 20x-23=7 | | 6(X+5m+4)= | | 9=5+2t | | 2[2y+5]=26 | | c=cx+n | | X^9/x^2 | | 2xy+6a=8x | | v^2+6-7=0 | | 19n=190 | | 3=2w-1 | | 7=v-8 | | -4k+2(5k-6)=-3k-38 | | 1/2(2)-3=y | | 2/3×9/20 | | -7v=140 | | D+30=9 | | C+24=-10 | | (8y-5w)= | | A-8=-14 | | 3q+1=7 | | (X^2+15-8x)=0 | | 5/11b=15 | | 8(x+1)=2(3x+5) | | H/5-19=2 | | 11(b-875)=517 | | x^3+3x^2=13x+9 | | 6log(x-3)=11 |